ANALISIS PERAMALAN EKSPOR INDONESIA PASCA KRISIS KEUANGAN EROPA DAN GLOBAL TAHUN 2008 DENGAN METODE DEKOMPOSISI - Jimmy Handoko Barus; Ramli Ramli (Ekonomi dan Keuangan, 2013)
ABSTRACT This research aims to analyze the value of Indonesia's exports of forecasting on agriculture, industry, mining, and the aggregate of the third sector in the aftermath of the financial crisis in Europe and globally in 2008 with the decomposition method. In this study, the data used is Indonesia export value growth data on agriculture, industry and mining, the aggregate of all three of these sectors during the period January 2002 s/d December 2011. This Data is used to predict the value of exports during the period January 2011 s/d December 2017 in the future by using the method of decomposition. In addition, the study also will try to prove the accuracy of the method of decomposition in forecasting Indonesia export value in the aggregate of all three of these sectors during the period January 2002 s/d December 2011. The results showed that the value of exports of agriculture, industry, mining, aggregate the third sector conducted by the method of decomposition for the period of January 2011 s/d December 2017 onwards produce export value that tends to increase. From the results of the measurement of the level of accuracy of forecasting the value of Indonesia's exports in the aggregate by the method of decomposition during the research period (January 2002 s/d December 2011), resulting MAPE value of 11%, which means that the accuracy of forecasting is not good because it exceeds the limits of the tolerance of 5 % Keywords : Agricultural Exports, Industrial Exports, Mining Exports, Financial Crisis,   Decomposition.